Dietary inclusion of ruminally protected linseed oil as a means to mitigate heat and slaughter-induced stress in feedlot cattle - Ceconi, Irene; Pighin, Darío Gabriel; Davies, Patricio; Cunzolo, Sebastián Abel; Pazos, Adriana Alejandra; Grigioni, Gabriela Maria (Oxford University Press, 2022)
There is evidence of a relationship between increased energy intake and the development of metabolic inflammation and insulin resistance (IR), and between the aforementioned metabolic state and impaired tolerance to heat stress. Based on the anti-inflammatory properties and mitigating effects on IR and stress of n-3 polyunsaturated fatty acids (n-3 PUFA), an experiment was performed to evaluate the effect of n-3 PUFA supplementation to feedlot-finished steers during summer on animal performance, physiological and biochemical variables associated with glucose metabolism, heat and preslaughter-induced stress, and meat quality. A total of 48 Angus steers (388 ± 2 kg) were fed one of three corn-based finishing diets containing (dry matter basis) 0% added oil (CON; negative control), or 1.90% of sunflower oil-calcium salt (SUN; positive control), or 1.92% of linseed oil-calcium salt (LIN). There was a trend (P = 0.08) for greater dry matter intake (DMI) and greater (P = 0.02) average daily gain (ADG) in LIN-fed animals compared with the average between those that received the CON or SUN diets, whereas no differences (P ≥ 0.34) were observed between the latter. No other performance, physiological, or carcass variables were affected (P ≥ 0.12) by treatment. Blood glucose and insulin were similar (P ≥ 0.14), though the homeostatic model assessment (HOMA) which gauges IR tended (P = 0.06) to be reduced for LIN-fed animals compared with the average between those that received the CON or SUN diets. Blood insulin and HOMA increased linearly (P ≤ 0.01) with days on feed. An interaction between the study phase (feeding period or slaughter) and treatment was observed (P ≤ 0.05) for glucose and cortisol. While the magnitude of glucose increase (P < 0.01) from the end of the feeding period to slaughter was greater for CON- and SUN-fed animals compared with LIN-fed ones, cortisol increased (P < 0.05) only in animals that received CON or SUN diets. Meat quality attributes were not affected (P ≥ 0.16) by treatment. The concentration of n-3 PUFA was greater (P < 0.01) and n-6:n-3 ratio was lesser (P < 0.01) in meat from LIN-fed animals compared with that resulting from the average between the animals that received the negative (CON) or positive (SUN) control diets. Results suggest that n-3 PUFA supplementation mitigated metabolic alterations associated with IR and preslaughter-related stress. It may have also improved tolerance to heat, resulting in greater DMI and ADG of steers fed a high-energy diet during summer. Results also indicate that glucose metabolism and heat stress tolerance worsen with time when feeding concentrate-based diets.